ORGANIZATIONAL AND ECONOMIC MECHANISMS AND CONCEPTUAL DIRECTIONS OF TOURISM DEVELOPMENT IN THE REGION - Daminova Barno Esanovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article analyzes the organizational and economic mechanisms for the development of the tourism sector in the regions and develops conceptual directions that serve its sustainable development. Particular attention is paid to the modernization of tourism infrastructure, attracting investments, public-private partnerships, local brands and the development of ecological tourism. The need to develop regional tourism strategies based on territorial characteristics, existing tourist resources, demographic factors and economic opportunities is substantiated.